Entrepreneurship training in tertiary education: Its development and transfer. (August 2015) - Jackson, Tony
Self-employment is becoming an increasingly viable option for growing numbers of young people entering the labour market, so it is important to identify and develop good practice in the delivery of entrepreneurship training. Not only will this enhance the quality of its provision, but it will also serve to ensure that the economic benefits from larger numbers of start-ups and innovatory new businesses are fully realised. The development and transfer of training in entrepreneurship are examined. Recent studies indicate that its provision at the tertiary education level boosts new business formation, and that experiential learning in entrepreneurship provides students with more incentives to start their own enterprises on graduating than formal enrolment in business programmes. These studies further suggest a strong positive correlation between those European universities that have adopted strategies, resources and institutional infrastructures explicitly targeted towards entrepreneurial objectives and the quality of their entrepreneurship training provision. On this basis, tertiary education institutions need to adopt a holistic cross-disciplinary approach, which commits them fully to promoting opportunities for training students in the formation of enterprises and the translation of innovatory ideas into operational businesses. To be effective, this should involve campus-wide provision, as well as outreach and engagement with the community and its businesses. Evidence demonstrates a number of alternative pathways for the transfer of good practice entrepreneurship training to less developed countries. Bottom-up models depend on the establishment of centres of excellence. These need to develop the capacity to engage with their own government policy-makers in shaping national training initiatives along their own good practice lines. Top-down models depend on creating a policy-framework and funding sources sufficient to encourage the adoption of effective entrepreneurship training programmes across the national educational framework. Here the crucial issue is the ability of existing institutions to respond to such opportunities. Between these extremes, the German dual VET system offers an 'off-the-shelf' option for the transfer of vocational entrepreneurship training to less developed countries, which still requires extensive adaptation to local conditions.